Bibliometric Analysis of Contemporary Trends in Earnings Management - Novita, Wellia; Hamidi, Masyhuri; Alfarisy, Moh Fany; Suhanda, Suhanda (SAFE-Network, 2025)
This study conducts a bibliometric analysis to investigate contemporary trends in earnings management research from 2019 to 2024. It aims to identify the dominant themes, authorship patterns, and thematic developments within the field. Using 139 Scopus indexed articles, the study applies VOSviewer to visualize keyword co-occurrence, author collaboration, and citation networks. The primary focus is on the intersection of earnings management with corporate governance, financial distress, and emerging markets. Results show that “earnings management” is the most frequently occurring keyword, followed by “real earnings management,” “corporate governance,” and “financial distress.” Thematic clusters indicate a persistent concern with how governance mechanisms and financial pressures influence earnings manipulation. The analysis also finds that scholarly collaboration is fragmented, with limited cross institutional or international co-authorship. While some authors, such as Duong Thi Chi and Elena Fernandez Rodriguez, play central roles within their clusters, overall integration across networks remains low. Emerging themes such as “board gender diversity,” “tax avoidance,” and “COVID-19 pandemic” point to evolving research priorities. This study contributes to the literature by synthesizing research trends, identifying knowledge gaps, and suggesting areas for future inquiry, particularly in the context of underexplored regions and institutional settings. The findings provide a comprehensive overview of the research landscape and offer valuable implications for academics, regulators, and practitioners.